Transformation of The Islamic Education System in Islamic Boarding Schools - Moh. Luthfi; Muhammad Farih (Institut Attanwir Bojonegoro, 2024)
Education plays a very important role in ensuring the survival of the state and nation. Implementation of education must be able to adapt to the surrounding circumstances. therefore educational transformation is a necessity. Islamic boarding school Ihyaul Ulum Manyar Sekaran Lamongan is one of the educational institutions that has been transformed from time so that it can be in harmony with the times. what is the background, how the process of transformation, the results of the transformation that has been carried out by the Ihyaul Ulum Islamic boarding school are interesting things to study more deeply. This study uses a case study technique and is qualitative in nature. This research is field research (Field Research) using a qualitative analysis approach, namely research that intends to understand the phenomenon of what is experienced by the research subject as a whole by describing it in the form of words and language, in a special natural context. observation, documentation and interview methods were used to collect data in this study. The educational transformation that took place in the Ihyaul Ulum Manyar Lamongan Islamic boarding school was motivated by:first, the quality of students' understanding of religion through classical books is still not optimal and has the potential to be developed.Second, demands from the community for Islamic boarding schools that do not only focus on religious knowledge, but also understand general knowledge, especially the recognition of formal diplomas. Curriculum transformation is carried out through several stages as follows: 1) Ihyaul Ulum Manyar Islamic Boarding School Curriculum Planning 2) Independent Curriculum Organization 3) Independent Curriculum Implementation. Pondok Pesantren Ihyaul Ulum has been transformed into an educational institution using an integral or combined curriculum system, namely the classic book system with a modern learning model. The positive impacts of educational transformation are as follows: 1) The religious basis is stronger 2) What is taught in the pesantren is more relevant to students 3) It is more free to determine the needs of students 4) The characteristics of the Islamic boarding school are more visible 5) Using classic books according to student needs . While the negative impacts are: 1) Less prepared students for curriculum changes 2) Lack of competent teaching staff in implementing the new curriculum 3) difficulties in controlling student administration. 4) limited infrastructure. 5) There is friction between certified teachers and teachers who are not certified. 6) Lack of land that should be used for the expansion of pesantren or formal institutions